Preparation, Characterization and In vitro Evaluation of Solid Dispersion Formulation of Clopidogrel Using Hydrophilic Polymers - Hossain, ASM Monjur Al; Koly, Fahima Jannat; Roy, Sajib Chandra; Kumar, Uttom; Hasanuzzaman, Md; Islam, Dipa (Dhaka University Journal of Pharmaceutical Sciences, 2024)
Clopidogrel bisulfate is a BCS class II drug with low water solubility leading to problematic dissolution behavior for oral drug delivery. The solid dispersion method was used to investigate the improvement of the dissolution profile of clopidogrel. Solid dispersions of clopidogrel were formulated using two polymers, PEG 6000 and poloxamer 188, at varying ratios through physical mixing and solvent evaporation techniques. A low-cost UV-Vis spectroscopic analytical method was developed at a λmax of 219 nm and validated following ICH guidelines. The dissolution of clopidogrel from solid dispersion improved significantly compared to pure drug, fitting most of the kinetics into the Korsmeyer-Peppas model. Comparisons showed that the binary solid dispersion formulation with clopidogrel: poloxmaer 188 at a ratio of 1:5 made via solvent evaporation method had the highest drug dissolution of 90.38% after 60 minutes, whereas the dissolution of pure clopidogrel was only about 66.67% in HCl media at pH 2. Characterization of prepared solid dispersions using FTIR, DSC, TGA and SEM confirmed the conversion of clopidogrel from crystalline to amorphous form. Dhaka Univ. J. Pharm. Sci. 23(2): 123-134, 2024 (December)